FORECASTING TECHNIQUE USING JUDMENTAL AND TIME SEQUENCE IN HOSTING SERVICE SELECTION - Prasetyo, Prasetyo (Universitas Gunadarma, 2008)
In the Internet era, selection of hosting services becomes very important. Most of the approaches in choosing hosting services are based on price and advertising. In this paper, prediction approach is used to select proper hosting services. Forecasting of Internet services users is conducted using combination of two methods, namely judgemental technique and time series. Judgemental technique was used when a website were about to be hosted for the first time by collecting opinions from those who have used the hosting services as an input in selecting which services are actually fit the needs. Meanwhile, time series technique can be used for forecasting trends of a website by analyzing the log file. The results of this paper is a recommendation related to decision which can be chosen to select the proper services for a website.Keyword(s) : Hosting, Judgemental, fore-casting, Time series, Website.Subject Description : C.2.Computer Communication Network | C.2.5.LAN-WAN | Internet